基于Unigraphics的V带轮三维设计系统的研究 - 孟庆尧; 张静; 贾奎连 (Jixie Chuandong, 2006)
UG/OPEN API , GRIP and UIStyler are utilized to create general programs for solving the modeling and assemblies of pulley. By the programs, the design of pulley can be simplified and files of part can be directly generated, so working efficiency in the farm machinery design can be raised.